High Level of Progesteron Receptor Membrane Component 1 (PGRMC 1) in Tissue of Breast Cancer Patients is Associated with Worse Response to Anthracycline-Based Neoadjuvant Therapy - Willibald, Marina; Wurster, Isabel; Meisner, Christoph; Vogel, Ulrich; Seeger, Harald; Mueck, Alfred O.; Fehm, Tanja; Neubauer, Hans (Hormone and Metabolic Research, 2017)
PGRMC1 is known to be highly expressed in breast cancer tissue and is associated with chemoresistance in breast cancer cells. However, its role in breast cancer signaling is not fully understood yet. In the present study, the expression status of PGRMC1 and its phosphorylated version (pPGRMC1) in breast cancer tissue and surrounding stroma before and after neoadjuvant therapy was examined to find a possible association to therapy response. Tissue biopsies of 69 breast cancer patients were analyzed by immunohistochemistry for expression levels of PGRMC1 and pPGRMC1. Expression status of PGRMC1 and pPGRMC1 in tumor tissue was compared with expression status of progesterone receptor (PR), estrogen receptor α (ERα), total estrogen receptor β (ERβ), ERβ1, ERβ2, the proliferation marker Ki-67, and human epidermal growth factor receptor 2 (HER2/neu). Correlations were calculated for expression of PGRMC1 and pPGRMC1 before and after neoadjuvant-therapy. PGRMC1 and pPGRMC1 were highly abundant in every breast cancer tissue sample. Considerably lower signals were detected in surrounding tissue. Further, PGRMC1 and pPGRMC1 abundance was found to correlate with ERβ expression. A lower level of pPGRMC1 could be found in post-therapy surgical specimens compared to specimens before treatment. Interestingly, patients with high PGRMC1 tumor levels showed worse response to anthracycline-based therapy as patients with lower PGRMC1 levels. These new findings demonstrate that PGRMC1 might play an important role in progression and therapy resistance of human breast tumors and could offer an interesting target for anticancer therapy.
Keywords: PGRMC1; hormone receptors; estrogen receptors; breast cancer therapy; chemoresistance